Health Concepts in Medicine and the Role of Philosophy - Elisabetta Lalumera (Philosophy of Medicine)
Philosophers interested in medicine and healthcare research should focus on the choice of health concepts. Conceptual choice is akin to conceptual engineering but, in addition to assessing whether a concept suits an objective, or offering a better one, it evaluates objectives, ranks them, and discusses stakeholders’ entitlement. To show the importance of choosing health concepts, I summarize the internal debate in medicine, showcasing definitions, constructs, and scales. To argue it is a philosophical task, I analyze the medical controversy over health as adaptation and self-management. I conclude with a to-do list of conceptual choice tasks, generalizable beyond medicine.